Features of Government Lending to Agricultural Entities and Their Influence on Supply Chain Management Strategies - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V. (ExcelingTech Publishers, 2019)
The article is devoted to the study of the influence of government lending to agricultural entities on the choice of the correct strategy of supply chain management in the production of products. We have defined the concept and features of government lending to agricultural entities. The current state of government lending to agricultural entities has been described. The main strategies of supply chain management have been analyzed. The economic indicators of the influence of government lending to agricultural entities and its influence on the choice of supply chain management strategy have been determined. As a result, the efficiency of public lending to agricultural entities has been made and proposals for improving the efficiency of supply chain management have been suggested.

Стаття присвячена дослідженню впливу державного кредитування суб’єктів АПК на вибір правильної стратегії управління ланцюгом поставок у виробництві продукції. Ми визначили поняття та особливості державного кредитування суб’єктів сільськогосподарської діяльності. Описано сучасний стан державного кредитування суб’єктів сільськогосподарської діяльності. Проаналізовано основні стратегії управління ланцюгом поставок. Визначено економічні показники впливу державного кредитування суб’єктів АПК та його вплив на вибір стратегії управління ланцюгом поставок. В результаті сформовано ефективність державного кредитування суб’єктів сільськогосподарської діяльності та запропоновано пропозиції щодо підвищення ефективності управління ланцюгом поставок.
Petrunenko I. V. Features of Government Lending to Agricultural Entities and Their Influence on Supply Chain Management Strategies / I. V. Petrunenko // International Journal of Supply Chain Management. - Vol. 8. - No. 4. - ExcelingTech Publishers, 2019. - P. 703-708.
Keywords: lending; public lending; agricultural entity; economic efficiency; supply chain management; кредитування; державне кредитування; сільськогосподарський суб'єкт; економічна ефективність; управління ланцюгом поставок; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES::Business and economics